A REVISION OF MACARONESIAN RUBUS TAXA (ROSACEAE) - MATZKE-HAJEK, G. (Edinburgh Journal of Botany, 2001)
The taxonomy and nomenclature of the Rubus species (sub)endemic to Madeira and the Azores are treated. Only three species names have to be retained: R. bollei Focke (synonyms: R. canariensis Focke, R. concolor Lowe, R. suspiciosus Menezes, R. vahlii Frid.), R. hochstetterorum Seub., and R. serrae Soldano (R. grandifolius Lowe). The last two species are described and illustrated. Three names are lectotypified. A key to Rubus of the Macaronesian region (five native species, one hybrid, one neophyte) is provided.